2007
DOI: 10.1136/jnnp.2006.112227
|View full text |Cite
|
Sign up to set email alerts
|

Familial occurrence of brain arteriovenous malformations: a systematic review

Abstract: Background: Brain arteriovenous malformations (BAVMs) are thought to be sporadic developmental vascular lesions, but familial occurrence has been described. We compared the characteristics of patients with familial BAVMs with those of patients with sporadic BAVMs. Methods: We systematically reviewed the literature on patients with familial BAVMs. Three families that were found in our centre were added. Age, sex distribution and clinical presentation of the identified patients were compared with those in popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 52 publications
0
83
1
Order By: Relevance
“…The prevalence of AVM is estimated to be approximately 0.01% and the detection rate ranges between 1.12-1.34 per 100 000 person years [1,2]. Although most cases of AVM are sporadic, a total of 53 patients from 25 families have been reported [4]. Familial brain AVM is defined when it occurs in two or more relatives (up to third-degree relative) in a family without associated disorders such as hereditary hemorrhagic telangiectasia (HHT), is autosomal dominant multisystemic vascular dysplasia [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of AVM is estimated to be approximately 0.01% and the detection rate ranges between 1.12-1.34 per 100 000 person years [1,2]. Although most cases of AVM are sporadic, a total of 53 patients from 25 families have been reported [4]. Familial brain AVM is defined when it occurs in two or more relatives (up to third-degree relative) in a family without associated disorders such as hereditary hemorrhagic telangiectasia (HHT), is autosomal dominant multisystemic vascular dysplasia [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Although most cases of AVM are sporadic, a total of 53 patients from 25 families have been reported [4]. Familial brain AVM is defined when it occurs in two or more relatives (up to third-degree relative) in a family without associated disorders such as hereditary hemorrhagic telangiectasia (HHT), is autosomal dominant multisystemic vascular dysplasia [4,5]. It is plausible that familial cases are more frequent and could be overlooked because of asymptomatic conditions in other relatives.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported an association with conditions such as hereditary hemorrhagic telangiectasia, Sturge-Weber disease, and WyburnMason syndrome. [6][7][8][9] AVMs often present with intracranial hemorrhage, but seizure, headache, and focal neurological deficits may also be seen. An annual hemorrhage risk of 2% to 4% is typically quoted and is associated with a 5% to 25% risk of death and 10% to 50% risk of neurological disability.…”
Section: Introductionmentioning
confidence: 99%
“…Although rare, familial cases of AVM outside the context of HHT have been reported in the literature [30,63]. A recent review article examined all case reports and identified 53 patients without HHT in 25 families with AVMs, mostly of first-degree relationships (79%) [63].…”
Section: Familial Aggregrationmentioning
confidence: 99%
“…A recent review article examined all case reports and identified 53 patients without HHT in 25 families with AVMs, mostly of first-degree relationships (79%) [63]. While no clear pattern of inheritance emerged from the pedigrees, the clinical characteristics of familial AVM patients did not differ significantly from sporadic AVM, except for a younger age at diagnosis.…”
Section: Familial Aggregrationmentioning
confidence: 99%